Influence of Nanofilled Polymer Coatings on Radiation Stability in Silicon Crystals Used in Solar Energy - L.P. Steblenko; A.A. Podolyan; L.M. Yashchenko; A.N. Kuryliuk; Yu.L. Kobzar; L.A. Voronzova; D.V. Kalinichenko; A.N. Krit; S.N. Naumenko (Журнал нано- та електронної фізики)
This paper investigates the changes in the decay kinetics of photovoltage due to the influence of low-energy (W = 8 keV) X-ray on the structure of the "solar" silicon + nanofilled polymer coatings. It is shown that radiation-stimulated degradation of the short-term and long-term components of decay, which are depended on the carriers’ lifetime on the surface and near-surface layers of "solar" silicon (s-Si) crystals accordingly, is absent for s-Si crystals with filler content (polysiloxane particles) in an amount of 0.5 wt. %. It is determined that the essential loss of radiation stability in s-Si crystals is observed when filler content (polysiloxane particles) in an amount of C  0,001 % and C  1 %.